DEVELOPING A TASK-BASED SYLLABUS BASED ON NEEDS ANALYSIS FOR MIDWIFERY AT UIN ALAUDDIN MAKASSAR - Dahniar Badruddin (Universitas Islam Negeri Alauddin Makassar, 2015)
This research aimed to develop a Task-Based syllabus for midwifery students of Midwifery Study Program at UIN Alauddin Makassar. The research design used in this study was Research and Development (R & D). Types of data obtained in this study were qualitative and quantitative. The qualitative data gained from interviewing students, graduate, and from the experts validation; meanwhile the quantitative data gained from the questionnaire which was distributed to the students. The instruments used in this study were questionnaire, interview guideline and rubric. The result of this research showed that 1) language needs of the students cover language skills and learning preferences. In language skills, speaking, listening, writing, reading are used often. In learning preferences, learning preferences in terms of learning English with others, others are study in small group, and study in big group, self study, study in pairs, while learning preferences in terms of learning by using teaching technique, study trough listening and speaking is mostly preferred by the students. 2) Language function used of graduate in the workplace is pregnancy, during pregnancy, good food for pregnant woman, diet in pregnancy, how to cut the umbilical cord, medical equipment. 3) The design syllabus based on the students’ need. In this case, the researcher recommended a Task-Based Syllabus based on the students’ need. The components of syllabus were validated. After validation, the experts pointed out that some components of the syllabus were developed well, whereas some components should be revised: materials, learning activities/task, and time allotment. Some of the materials were changed with the appropriate materials whih was correlated with the topic, individual practice was needed to be added to the learning activities, time allotments should be distributed proportionally, and then the sources should be added.